Dakwah Bil-Hal Kiai sebagai Upaya Pemberdayaan Santri (Action Da'wah by the Kiai as an Effort to Empower Students) - Nor Kholis; M Mudhofi; Nur Hamid; Elvara Norma Aroyandin (Jurnal Dakwah Risalah, 2021)
This study aims to examine the role of Kyai in the effort to empower students through the bil-hal da'wah method at one of the Islamic boarding schools in Yogyakarta. This type of research is field research. Data were collected through interview and observation methods. Through the emic approach, data analysis was carried out descriptively - qualitatively. The study results show that the bil-hal da'wah method carried out by Kyai has a positive impact on the students. This can be seen through three aspects; First, changes in theological morality and social morality for the better. Second, to cultivate the mentality of personality and social care. Third, create productivity of economic independence. However, it is still necessary to continue improving the students' competency skills (Human Resources). Apart from the shortcomings, the bil-hal da'wah method can be used as a role model for developing constructive da'wah, both for students and the wider community.